Knockdown of circRNA circ_0087378 Represses the Tumorigenesis and Progression of Esophageal Squamous Cell Carcinoma Through Modulating the miR-140-3p/E2F3 Axis - Wang, Jing; Wang, Qiushuang; Gong, Yi; Hu, Qiu; Zhang, Haoliang; Ke, Shaobo; Chen, Yongshun (Frontiers in Oncology, 2021)
Background: We aimed to investigate the function and underlying mechanisms of circ_0087378 in esophageal squamous cell carcinoma (ESCC). Methods: We verified higher circ_0087378 expression in ESCC tissues by performing qRT-PCR assays. We further confirmed the oncogenic roles of circ_0087378 in ESCC cells through a series of biological function assays. Then, we used an RNA pull-down assay and luciferase reporter assay to identify miR-140-3p that directly interacts with circ_0087378. Subsequent studies were performed to demonstrate that the circ_0087378/miR-140-3p/E2F3 axis promotes ESCC development. Results: We demonstrated that upregulated circ_0087378 expression was positively associated with tumor size, histological grade, tumor stage, the presence of metastasis and worse survival in patients with ESCC. Our results further revealed that knockdown of circ_0087378 suppressed the proliferation, migration and invasion of ESCC cells and reduced tumor growth in vivo. Mechanistically, we showed that circ_0087378 could directly bind to miR-miR-140-3p and relieve the suppression for target E2F3, which accelerated cell proliferation, migration and invasion. Correlation analysis in ESCC specimens supported the involvement of the circ_0087378/miR-140-3p/E2F3 axis in ESCC progression. Conclusions: This study demonstrated that circ_0087378 might act as a competing endogenous RNA for miR-140-3p, which could inhibit the tumorigenesis and progression of ESCC through upregulating E2F3 expression.